2019
DOI: 10.1084/jem.20190580
|View full text |Cite
|
Sign up to set email alerts
|

The human fetal thymus generates invariant effector γδ T cells

Abstract: In the mouse thymus, invariant γδ T cells are generated at well-defined times during development and acquire effector functions before exiting the thymus. However, whether such thymic programming and age-dependent generation of invariant γδ T cells occur in humans is not known. Here we found that, unlike postnatal γδ thymocytes, human fetal γδ thymocytes were functionally programmed (e.g., IFNγ, granzymes) and expressed low levels of terminal deoxynucleotidyl transferase (TdT). This low level of TdT resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
137
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(154 citation statements)
references
References 90 publications
(138 reference statements)
8
137
3
Order By: Relevance
“…The earliest T cells, namely the subset of pAg-specific Vγ9Vδ2 + T cells, are followed by Vδ1 + T cells that can be detected in fetal blood at week 25 and increase to become the major population of γδ T cells at term-delivery [37,62,67] (Figure 1). The γδ TCR repertoire of fetal non-Vγ9Vδ2 + thymocytes was shown to comprise an oligoclonal TRG repertoire, a diverse TRGV usage (including the non-functional TRGV10) and usage of mainly TRDV2 rearrangements paired with TRDJ2 or TRDJ3 [36]. Those fetal thymocytes use few N insertions, and TdT expression at this stage is low [36].…”
Section: γδ T Cell Subsets Arise Early During Ontogenymentioning
confidence: 99%
See 3 more Smart Citations
“…The earliest T cells, namely the subset of pAg-specific Vγ9Vδ2 + T cells, are followed by Vδ1 + T cells that can be detected in fetal blood at week 25 and increase to become the major population of γδ T cells at term-delivery [37,62,67] (Figure 1). The γδ TCR repertoire of fetal non-Vγ9Vδ2 + thymocytes was shown to comprise an oligoclonal TRG repertoire, a diverse TRGV usage (including the non-functional TRGV10) and usage of mainly TRDV2 rearrangements paired with TRDJ2 or TRDJ3 [36]. Those fetal thymocytes use few N insertions, and TdT expression at this stage is low [36].…”
Section: γδ T Cell Subsets Arise Early During Ontogenymentioning
confidence: 99%
“…The γδ TCR repertoire of fetal non-Vγ9Vδ2 + thymocytes was shown to comprise an oligoclonal TRG repertoire, a diverse TRGV usage (including the non-functional TRGV10) and usage of mainly TRDV2 rearrangements paired with TRDJ2 or TRDJ3 [36]. Those fetal thymocytes use few N insertions, and TdT expression at this stage is low [36]. Similar to germline-encoded Vγ9JP rearrangements, invariant TCRs (TRGV8JP1, TRGV10JP1, TRDV2D3, TRDV1D3) were found to be expressed by fetal non-Vγ9Vδ2 + thymocytes, and recombination is thought to be similarly dictated by short homology repeats [36].…”
Section: γδ T Cell Subsets Arise Early During Ontogenymentioning
confidence: 99%
See 2 more Smart Citations
“…γδ TCR gene rearrangement can be detected by embryonic day 14 in the mouse thymus, week 8 in humans, and canonical subsets can also be detected extrathymically in both species during fetal development [111][112][113]. In the human fetus, the Vγ9+Vδ2+ subset is among the first T cell subset to be developed and this population further expands during childhood, although these cells have a distinct lineage, as recent studies have shown that the ontogeny between fetal blood γδ and adult blood γδ is dissimilar [112,[114][115][116]. Vγ9 and Vδ2 V gene segments can be detected as early as 5 to 6 weeks gestation in the fetal liver and after 8 weeks in the fetal thymus [117].…”
Section: In Humansmentioning
confidence: 99%